Studying on the Emission Characteristic of a Diesel Engine by Simulation - Xiao, Youhong; Tian, Xinna; Zhou, Peilin (Asian Journal of Chemistry, 2012)
At present, the problem of environment pollution draws people's attention increasingly. The international communities and organizations established relevant laws to restrict the emission and reduce the harm to human being and environment. In this paper, a numerical simulation model for diesel engine was established by GT-POWER in order to study the NO, CO and HC emissions characteristic of the diesel engine and the model was validated by experimental data. Based on the model, the variable parameters including injection timing, intake air temperature, compression ratio and EGR ratio were carried out. The simulation results showed that with the decrease of CA BTDC, intake air temperature, compression ratio and EGR ratio respectively, the NO emission decreased. However, the CO and hydrocarbon emissions increased.